Revisiting the iron pools in cucumber roots: identification and localization - Kovács, Krisztina; Pechoušek, Jiří; Machala, Libor; Zbořil, Radek; Klencsár, Zoltán; Solti, Ádám; Tóth, Brigitta; Müller, Brigitta; Pham, Hong Diep; Kristóf, Zoltán; Fodor, Ferenc (Planta, 2016)
MAIN CONCLUSION: Fe deficiency responses in Strategy I causes a shift from the formation of partially removable hydrous ferric oxide on the root surface to the accumulation of Fe-citrate in the xylem. Iron may accumulate in various chemical forms during its uptake and assimilation in roots. The permanent and transient Fe microenvironments formed during these processes in cucumber which takes up Fe in a reduction based process (Strategy I) have been investigated. The identification of Fe microenvironments was carried out with (57)Fe Mössbauer spectroscopy and immunoblotting, whereas reductive washing and high-resolution microscopy was applied for the localization. In plants supplied with (57)Fe(III)-citrate, a transient presence of Fe-carboxylates in removable forms and the accumulation of partly removable, amorphous hydrous ferric oxide/hydroxyde have been identified in the apoplast and on the root surface, respectively. The latter may at least partly be the consequence of bacterial activity at the root surface. Ferritin accumulation did not occur at optimal Fe supply. Under Fe deficiency, highly soluble ferrous hexaaqua complex is transiently formed along with the accumulation of Fe-carboxylates, likely Fe-citrate. As (57)Fe-citrate is non-removable from the root samples of Fe deficient plants, the major site of accumulation is suggested to be the root xylem. Reductive washing results in another ferrous microenvironment remaining in the root apoplast, the Fe(II)-bipyridyl complex, which accounts for ~30 % of the total Fe content of the root samples treated for 10 min and rinsed with CaSO4 solution. When (57)Fe(III)-EDTA or (57)Fe(III)-EDDHA was applied as Fe-source higher soluble ferrous Fe accumulation was accompanied by a lower total Fe content, confirming that chelates are more efficient in maintaining soluble Fe in the medium while less stable natural complexes as Fe-citrate may perform better in Fe accumulation.
Keywords: Iron; Xylem; železo; spektroskopie Mossbauerova; Immunoblotting; xylém; Microscopy, Electron; Oxidation-Reduction; kořeny rostlin; elektronová mikroskopie; Ferric Compounds; sloučeniny železa; železité sloučeniny; imunoblotting; oxidace-redukce; Iron Compounds; Plant Roots; Cucumis sativus; Spectroscopy, Mossbauer